Sudden stop of capital flows and the consequences for the banking sector and the real economy - Florian Neagu; Irina Mihai (European Central Bank (ECB), 2013)
The paper develops a macro-prudential liquidity stress-testing tool in order to capture the possible consequences of a capital outflow (including a run of deposits). The tool includes a feedback from the banking sector to the real economy, incorporates a link between liquidity risk and solvency risk, and is tailored for emerging market features. The stress-testing tool aims to: (i) test the capacity of the banking sector to withstand the sudden stop of capital flows, and to gauge the consequences of the liquidity stress to the solvency ratio; (ii) quantify the liquidity deficit that a central bank should accommodate; (iii) assess the impact on credit supply when the sudden stop occurs; and (iv) support the implementation of an orderly disintermediation process. The macro-prudential tool is applied on the Romanian banking sector.
Keywords: G21; F32; 330; banks; emerging markets; macro-prudential tool; stress-testing; systemic liquidity